(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
This article provides information on the nature and objectives of veterinary-sanitary control,veterinary-sanitary control in companies that prepare, store and recycle raw materials, transportation of animals, livestock products and raw materials, and veterinary and sanitary control in export and import processes.